Cytochrome c Reductase is a Key Enzyme Involved in the Extracellular Electron Transfer Pathway towards Transition Metal Complexes in Pseudomonas Putida - Lai, Bin (John Wiley and Sons Inc., 2020)

(untitled) (ChemSusChem)
Mediator‐based extracellular electron transfer (EET) pathways can balance the redox metabolism of microbes. However, such electro‐biosynthesis processes are constrained by the unknown underlying EET mechanisms. In this paper, Pseudomonas putida was studied to systematically investigate its EET pathway to transition metal complexes (i. e., [Fe(CN)(6)](3−/4−) and [Co(bpy)(3)](3+/2+); bpy=2,2′‐bipyridyl) under anaerobic conditions. Comparative proteomics showed the aerobic respiratory components were upregulated in a bioelectrochemical system without oxygen, suggesting their potential contribution to EET. Further tests found inhibiting cytochrome c oxidase activity by NaN(3) and NADH dehydrogenase by rotenone did not significantly change the current output. However, the EET pathway was completely blocked, while cytochrome c reductase activity was inhibited by antimycin A. Although it cannot be excluded that cytochrome c and the periplasmic subunit of cytochrome c oxidase donate electrons to the transition metal complexes, these results strongly demonstrate that cytochrome c reductase is a key complex for the EET pathway.